ANALYSIS OF AIR-COOLED CONDENSER EFFECTIVENESS UNDER TROPICAL AMBIENT TEMPERATURE VARIATIONS IN LOW-ENTHALPY GEOTHERMAL SYSTEMS - Richard Alexander; Agus Setyawan; Udi Harmoko (Trends in Mechanical Engineering Research, 2026)
The performance of Air-Cooled Condensers (ACC) in low-enthalpy geothermal systems is strongly influenced by ambient temperature as the primary cooling medium. This study analyzes the effect of tropical ambient temperature variations on ACC effectiveness using the effectiveness-NTU method and linear regression based on 1,415 operational data points. The results show that the calculated ACC effectiveness ranges from 49.93% to 64.46% within an ambient temperature range of 18.63°C to 29.56°C. Ambient temperature shows a very strong positive correlation with ACC effectiveness, with r = 0.9984 and R² = 0.9967. The increase in effectiveness at higher ambient temperatures is associated with a reduction in the theoretical maximum heat transfer rate (Qmax), rather than an improvement in actual cooling performance. The developed model can be used as a simple predictive tool for operational management of low-enthalpy geothermal systems in tropical regions.